Comparing Biochemical and Raman Microscopy Analyses of Starch, Lipids, Polyphosphate, and Guanine Pools during the Cell Cycle of Desmodesmus quadricauda - Moudříková, Šárka; Ivanov, Ivan Nedyalkov; Vítová, Milada; Nedbal, Ladislav; Zachleder, Vilém; Mojzeš, Peter; Bišová, Kateřina (Cells, 2021)
Photosynthetic energy conversion and the resulting photoautotrophic growth of green algae can only occur in daylight, but DNA replication, nuclear and cellular divisions occur often during the night. With such a light/dark regime, an algal culture becomes synchronized. In this study, using synchronized cultures of the green alga Desmodesmus quadricauda, the dynamics of starch, lipid, polyphosphate, and guanine pools were investigated during the cell cycle by two independent methodologies; conventional biochemical analyzes of cell suspensions and confocal Raman microscopy of single algal cells. Raman microscopy reports not only on mean concentrations, but also on the distribution of pools within cells. This is more sensitive in detecting lipids than biochemical analysis, but both methods-as well as conventional fluorescence microscopy-were comparable in detecting polyphosphates. Discrepancies in the detection of starch by Raman microscopy are discussed. The power of Raman microscopy was proven to be particularly valuable in the detection of guanine, which was traceable by its unique vibrational signature. Guanine microcrystals occurred specifically at around the time of DNA replication and prior to nuclear division. Interestingly, guanine crystals co-localized with polyphosphates in the vicinity of nuclei around the time of nuclear division.
Keywords: Cell Cycle; škrob; lipidy; Spectrum Analysis, Raman; guanin; Guanine; starch; Time Factors; confocal Raman microscopy; lipids; Starch; polyphosphate; buněčná stěna; Cell Size; buněčný cyklus; velikost buňky; Lipids; lipidová tělíska; guanine; microalgae; Microscopy; Desmodesmus quadricauda; Cell Wall; Lipid Droplets; polyfosfáty; časové faktory; Polyphosphates; mikroskopie; Ramanova spektroskopie; cell cycle; Chlorophyta